A Phytol‐Enriched Diet Activates PPAR‐α in the Liver and Brown Adipose Tissue to Ameliorate Obesity‐Induced Metabolic Abnormalities. Issue 6 (22nd February 2018) - An, Ji‐Yeong; Jheng, Huei‐Fen; Nagai, Hiroyuki; Sanada, Kohei; Takahashi, Haruya; Iwase, Mari; Watanabe, Natsumi; Kim, Young‐Il; Teraminami, Aki; Takahashi, Nobuyuki; Nakata, Rieko; Inoue, Hiroyasu; et al.
Abstract : Scope: Peroxisome proliferator‐activated receptor alpha (PPAR‐α) is a ligand‐activated transcription factor that regulates lipid and carbohydrate metabolism. We investigate the effects of naturally occurring PPAR‐α agonists, phytol, and its metabolite phytanic acid, on obesity‐induced metabolic disorders using a mouse model. Methods and results: A luciferase reporter assay shows that phytanic acid potently activates PPAR‐α among PPAR subtypes. In high‐fat‐diet‐induced, severely obese mice, a phytol‐enriched diet increases phytanic acid levels in the liver and adipose tissue, where PPAR‐α is abundantly expressed. A phytol‐enriched diet ameliorates severe obesity and the related metabolic abnormalities of white adipose tissue. Moreover, the expression of PPAR‐α target genes in the liver and brown adipose tissue is enhanced by a phytol‐enriched diet, suggesting that phytol and phytanic acid activate PPAR‐α in these organs. We confirm that phytanic acid treatment induced PPAR‐α target gene expression in both primary hepatocytes and brown adipocytes from wild‐type mice, but not in these cells from PPAR‐α‐deficient mice. Conclusion: A phytol‐enriched diet may increase phytanic acid levels in the liver and brown adipocytes, thereby activating PPAR‐α in these organs and ameliorating obesity‐induced metabolic diseases. Abstract : The regulation of lipid metabolism by phytol and its metabolite phytanic acid in the liver and brown adipose tissue (BAT). Phytol is converted into phytanic acid. Phytanic acid enhance fatty acid oxidation via the activation of PPAR‐α in the liver and BAT. These dual actions in the liver and BAT attenuate adipocyte hypertrophy and chronic inflammation in white adipose tissue (WAT), leading to the prevention of adipocyte dysfunctions. As a consequence, it improves insulin resistance and obesity.